Challenges and Opportunities in Using Social Media to Build Digital Literacy in Public Education: A Review-Based Perspective - Evimawati Harefa; Alexius Poto Obe; Bartolomeus Sihite; Megawati Naibaho; Ester Fosumange Laia; Marlinus Gaurifa; Raimon Rozaman Bawamenewi; Agnes Taratangbuk; Rikki Makkirap Simamora; Iman Suryani Ndraha; Nicolas Febriso Naibaho (Postgraduate, University of Mataram, 2025)
The advancement of technology that continues to develop today can help accelerate and simplify human work. Technological progress facilitates communication without limitations of space and time. Easy internet access makes it easier to obtain various types of information. However, the vast amount of information available online can also lead to the spread of hoaxes and misinformation. This makes digital literacy crucial for the public to distinguish between valid and invalid information. Social media, as an easily accessible form of information technology, can serve as an educational medium for promoting digital literacy. Social media as a model for digital literacy can also be applied in science education by providing students with worksheets and asking them to review information found on social media related to specific science topics. This approach not only strengthens students’ digital literacy skills but also deepens their understanding of scientific concepts by connecting them with real-world issues and current information trends. The method used is descriptive qualitative, with data derived from previous research conducted over the past ten years. The results show that digital literacy is essential for communities in utilizing technology effectively. A high level of digital literacy enables individuals to differentiate between accurate and inaccurate information. The opportunities for using social media in digital literacy education include enhanced collaborative communication, engagement and accessibility, empowerment, lifelong learning, and the promotion of innovative educational practices. The challenges, however, include limited access and resource constraints, barriers to digital literacy, privacy and security concerns, and ethical and professional considerations. These findings support the strategic integration of social media into public education systems as a tool to enhance both scientific and digital literacy, especially among youth